Panorama da educação fundamental e média no Brasil: o modelo da aprendizagem baseada em problemas como experiência na prática docente - MALHEIRO, João Manoel da Silva (Universidade Federal do Pará, 2011)
The present document define the current profile of the Fundamental and High School in Brazil re-visiting the data base of official institutions (INEP and IBGE). We have found suspicious coincidences between, income concentration and educational abstinence, which we suggest is a fuel for the poverty cycle in our country. Qualitative aspects of the Brazilian school were also obtained in order to describe the difficulties to implement high quality education in Brazil at these levels. We also investigate through the case study methodology two summer courses designed to implement and test the Problem Based Learning (PBL). The classes were dedicated to teachers and students of High School. Using straight observation and inferences took from questionnaires applied to students and teachers, before and after each vacation course (in 2004 and 2005), the impact of the PBA over students and teachers was measured. The results revealed many difficulties and perplexities presented by the teachers and the students, such as the difficulty to relate experiments and contents from the text books, the almost complete abstinence of experimentation in the High School, difficulties to distinguishing hypothesis and fact, etc. The Problem Based Learning was accepted by all (students and teachers) as a possible way to change Science and Biology. However, its broad dissemination will demand qualification on a large scale, management and leadership to start the process of change, salary improvements and better infrastructure in the schools for experimentation. Using methodologies similar to the PBL, as an alternative for qualification, research universities need to be directly engaged in the process of renewal. An educational pact has to be built to reform the education and that action should include Managers and Teachers of Middle and High School, Secretaries of Education (from the State and the District), State and District Government, Ministries of Education and of Science and Technology, Research Universities and Fund Agencies, so that the effort can achieve national dimensions.